Detecção eletroquímica de ácidos urônicos presentes no bagaço de cana-de-açúcar utilizando eletrodo modificado com nanopartículas de cobre em técnica de HPLC - Beluomini, Maísa Azevedo [UNESP] (2013)
Uronic acid, D-glucuronic acid and D-galacturonic are found in lignocellulosic materials and can be used in the food industry and chemical industry. They are present in the fibrous structure of the sugarcane bagasse and are not oxidized at glassy carbon electrodes. For this we developed a detector modified with copper nanoparticles by potentiostatic electrodeposition. D-galacturonic acid and D-glucuronic irreversibly oxidize at potentials of 0.45 and 0.48 V vs. Ag/AgCl, respectively in cyclic voltammetry. Other voltammetric techniques such as differential pulse voltammetry and square wave voltammetry were also studied and the detection limit was in the order of 10-5 mol L-1 and amperometric sensitivity in the order of 10-4 mol L-1. The developed electrode was used in chromatography with pulsed amperometric detection in wall-jet cell. An anion exchange column, Carbo Pac PA10, was used for separation of uronic acids in isocratic conditions, mobile phase containing 0.1 mol L-1 NaOH and 0.28 mol L-1 CH3COO-Na+, the detection potential of 0.45 V vs. Pd and flow rate of 1.0 mL min-1. The separation of the acids was complete within 15 min. The detection limit was between 5.8x10-7 and 7.3x10-7 mol L-1, the amperometric sensitivity was 3.6 ± 1.8x106 and 1.9 ±1,0 x 106 mol L-1 to D-galacturonic acid and D-glucuronic, respectively. The method was applied to real samples of 300 mg of hydrolyzate bagasse. The value found in this sample was 15.8±0.5 g/kg of D-galacturonic acid and 12.5±0.5 g/kg to D-glucuronic acid. The results demonstrate that the proposed method can be used to detect these acids without the need for derivatization with the advantage of having fewer interfering, considerable accuracy.